Muscular adaptations in low- versus high-load resistance training: A meta-analysis. Issue 1 (2nd January 2016) - Schoenfeld, Brad J.; Wilson, Jacob M.; Lowery, Ryan P.; Krieger, James W.
Abstract: There has been much debate as to optimal loading strategies for maximising the adaptive response to resistance exercise. The purpose of this paper therefore was to conduct a meta-analysis of randomised controlled trials to compare the effects of low-load (≤60% 1 repetition maximum [RM]) versus high-load (≥65% 1 RM) training in enhancing post-exercise muscular adaptations. The strength analysis comprised 251 subjects and 32 effect sizes (ESs), nested within 20 treatment groups and 9 studies. The hypertrophy analysis comprised 191 subjects and 34 ESs, nested with 17 treatment groups and 8 studies. There was a trend for strength outcomes to be greater with high loads compared to low loads (difference = 1.07 ± 0.60; CI: −0.18, 2.32; p = 0.09). The mean ES for low loads was 1.23 ± 0.43 (CI: 0.32, 2.13). The mean ES for high loads was 2.30 ± 0.43 (CI: 1.41, 3.19). There was a trend for hypertrophy outcomes to be greater with high loads compared to low loads (difference = 0.43 ± 0.24; CI: −0.05, 0.92; p = 0.076). The mean ES for low loads was 0.39 ± 0.17 (CI: 0.05, 0.73). The mean ES for high loads was 0.82 ± 0.17 (CI: 0.49, 1.16). In conclusion, training with loads ≤50% 1 RM was found to promote substantial increases in muscle strength and hypertrophy in untrained individuals, but a trend was noted for superiority of heavy loading with respect to these outcome measures with null findings likely attributed to a relatively small number of studies on the topic.